Theater photograph in the reception and mediation of the spectator: what is seen, what is said and what is fact - Juliana Correia da Luz; Robson Rosseto (Travessias, 2019)
This article was built on an experience of reception and theatrical mediation, whose use of photography as a stimulus for capturing the expectations of the spectator was the methodological basis. The work exposes the investigative path of the photography potentialities as a pedagogical resource for the theatrical mediation of the Autômatos: Self da Inexistência spectacle, produced by Cia Laica de Teatro. The analysis of the data included answers from an interview conducted with spectators, boosted by the photograph reception (before the spectacle) and images/scenes of the spectacle itself (after the spectacle). The audience, as co-author of the scene, established connections between the perceptions derived from the photographs and the moment of the spectacle reception, promoting interactions with memories associated to the audience's fruition facing the theatrical event.